Logic Circuits Synthesis Through Genetic Algorithms - Reis, Cecília (2019)
This paper proposes a genetic algorithm for designing combinational logic circuits and studies four different case examples: the 2-to-1 multiplexer, the one-bit full adder, the four-bit parity checker and the two-bit multiplier. The objective of this work is to generate a functional circuit with the minimum number of logic gates. It is also studied the scalability problem that emerges from the exponential growth of the truth table when the circuits complexity increases. Furthermore, it is as well investigated the population size and the processing time for achieving a solution in order to establish a compromise between the two parameters.